2021
DOI: 10.12659/msm.932340
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Risk Factors for Intraoperative Acquired Pressure Injury in Patients Undergoing Neurosurgery: A Retrospective Single-Center Study

Abstract: Background Risk factors for intraoperative acquired pressure injury (IAPI) in patients undergoing various surgical procedures have been described in previous studies. However, whether risk factors for IAPI in patients undergoing neurosurgery differ remains unknown. The aim of the present study was to explore independent risk factors for IAPI in patients undergoing neurosurgery. Material/Methods Data from 465 patients who underwent neurosurgery between October 2017and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The study indicates that being overweight, prone and lateral positioning, use of a head frame and longer surgical times are associated with an increased risk of IAPI in patients undergoing neurosurgery. Prospective studies should be conducted to verify these findings and consideration should be given to the use of these factors in clinical practice to identify high‐risk patients 8 . These individuals have a high risk of IAPIs because their procedures are longer, continuous irrigation with saline is used during these surgeries and craniotomy requires the use of air and electric drills, which results in vibration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study indicates that being overweight, prone and lateral positioning, use of a head frame and longer surgical times are associated with an increased risk of IAPI in patients undergoing neurosurgery. Prospective studies should be conducted to verify these findings and consideration should be given to the use of these factors in clinical practice to identify high‐risk patients 8 . These individuals have a high risk of IAPIs because their procedures are longer, continuous irrigation with saline is used during these surgeries and craniotomy requires the use of air and electric drills, which results in vibration.…”
Section: Discussionmentioning
confidence: 99%
“…The use of intraoperative pneumatic drills, extensive water irrigation, mannitol dehydration, prone or lateral positioning, use of a head frame and operative times of 4-8 are all risk factors for IAPU in neurosurgery. [4][5][6][7][8] Surgical patient characteristics, such as age, diagnosis and body mass index (BMI), were significantly associated with IAPU(intraoperative skin pressure injuries). 9 Studies have shown that fluidized positioners applied to the occipital area of patients can prevent pressure damage to the occipital skin and hair loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to non-surgical patients admitted to the ICU, surgical patients may have some specific risk factors for the incidence of PI [ 26 ]. For instance, in a study of PI in patients undergoing neurosurgery, it was found that being overweight and having a longer surgical time was strongly associated with the occurrence of PI [ 27 ]. In another study about risk factors for PI in patients undergoing hepatobiliary surgery, prolonged operative time, open surgery, and intraoperative hypotension were found to be associated with an increased incidence of PI [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies draw attention to the risk of pressure injury for 2-5 hours or more (. The reason why it was taken over 60 minutes in this study was to include the cases in which general anesthesia was applied and to obtain a sample for statistical comparison (Wu et al, 2021;Webster et al, 2015;Aydin et al, 2021).…”
Section: Participantsmentioning
confidence: 99%